Ritual Penti di Tanah Diaspora: Komunitas Manggarai di Kalimantan Barat - Felomena Sunarti (Retorik: Jurnal Ilmu Humaniora, 2023)
In order to unite the Manggarai people in West Kalimantan, the Manggarai community leaders on behalf of the “Manggarai people” invited all Manggarai people to discuss the Penti ritual. The meeting resulted in an agreement to hold the Penti ritual. They received support from the Dayak Mualang community, so that the ritual could be carried out. This study describes the similarities and differences of the Penti rituals practiced in Flores and in West Kalimantan. The Penti ritual is held as a form of gratitude for the Manggarai people to God (Mori Keraeng) and their ancestors for their success abroad. The methodology used in this study is the ethnographic imagination methodology introduced by Paul Willis. Concepts used in the analysis of this study are the concepts of crossing and dwelling from Thomas A. Tweed and of liminality and communitas from Victor Turner. This study shows that the Penti ritual practiced by Manggarai people living outside their West Kalimantan hometowns contains important aspects, namely giving thanks to Mori Keraeng (God) and ancestors, fostering family relationships, and introducing the ritual to the younger generation of Manggarai in West Kalimantan.